2014
DOI: 10.4028/www.scientific.net/msf.787.102
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Steel Production

Abstract: Based on life cycle assessment, analysis of energy consumption and other environment load by steel production in Chinese typical iron and steel industry was carried out. The process accounted for the most environment load was found by studying the different processes in steel production route. The results indicate that the most important process is blast furnace (BF) which is the major factor of CO2 and CO emissions, and contributes most to globe warming potential (GWP) and photochemical ozone creation potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Similarly, the generation of energy such as coal, crude oil, natural gas [17], diesel oil, gasoline [18] and heavy oil [19], are all taken into account in the view of life cycle. In addition, the auxiliary materials such as steel [20] and limestone [21] were also considered in the system.…”
Section: Inventory Analysismentioning
confidence: 99%
“…Similarly, the generation of energy such as coal, crude oil, natural gas [17], diesel oil, gasoline [18] and heavy oil [19], are all taken into account in the view of life cycle. In addition, the auxiliary materials such as steel [20] and limestone [21] were also considered in the system.…”
Section: Inventory Analysismentioning
confidence: 99%
“…In addition, an LCA study on a steel industry in China found that the total impact on the global warming category was 1042.8 kg CO2 eq, slightly lower than the total impact on global warming in this study. However, in that study, the steel melting process used the basic oxygen furnace [13]. Figure 3 show the impact contribution of each raw material in the steel production process.…”
Section: Resultsmentioning
confidence: 99%
“…In Cut-off approach, PFP in BOF is 2.308kgCO 2 e/kg, the main materials of input and output as shown in Figure 1; A, B, C, D plants' PFP are 0.996, 1.002, 1.044, 1.072kgCO 2 e/kg, respectively [19]. Computational process of waste valuable method is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%